Integrated farming system for marginal landholders A lane towards livelihood security - Shyam, C. S.; Bapatla, Kiran Gandhi; Gayatri, Bandaru; Rao, Karnena Koteswara; Panda, Bipin Bihari (Indian Farming, 2025)
Marginal landholders, who own less than one hectare of land, make up a significant portion of the total landholders in the country and face the challenge of securing year-round income and employment. Integrated Farming System (IFS), which emphasizes enterprise diversification, offers a promising solution by boosting productivity per unit area while meeting the nutritional needs of farming families. The diverse components in the IFS model not only provides consistent employment throughout the year but also ensures regular income. Moreover, IFS leads to a higher marketable surplus with a range of products. When efficiently implemented, it serves as a viable solution to the challenges faced by marginal farmers.